2006
DOI: 10.1111/j.1553-2712.2006.tb00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Point-of-care Influenza Testing on Management of Febrile Children

Abstract: When using a strategy of performing influenza testing on all patients at risk for SBI who presented to a pediatric ED during an influenza outbreak, the method of testing (POCT or ST) did not appear to significantly alter physician management, cost, or length of stay in the pediatric ED. However, if the interaction of the method of testing and the test result (positive or negative) were considered, a positive POCT for influenza was associated with a significant reduction in orders for urinalyses and urine cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 27 publications
2
47
1
Order By: Relevance
“…No differences were seen among those who did not have influenza. A quasi-randomized trial of influenza rapid testing showed similar results [51]. When the analysis included all children, the use of a rapid test did not influence clinician behavior.…”
Section: Potential Benefits Of Multiplex Diagnosticsmentioning
confidence: 75%
“…No differences were seen among those who did not have influenza. A quasi-randomized trial of influenza rapid testing showed similar results [51]. When the analysis included all children, the use of a rapid test did not influence clinician behavior.…”
Section: Potential Benefits Of Multiplex Diagnosticsmentioning
confidence: 75%
“…Even though multiplex PCR assays can detect several different viruses simultaneously and rapidly, their advantages in terms of cost reduction over other rapid diagnostic assays (DFA, antigen detection) are still unclear. When rapid antigenic diagnostic tests for viral infections became widely used, several studies demonstrated their clinical utility in reducing length of hospital stay, performance of ancillary diagnostic tests and antibiotic consumption among pediatric (Bonner et al, 2003;Esposito et al, 2003;Sharma, 2002;Woo et al, 1997) (Abanses et al, 2006;Benito-FernĂĄndez et al, 2006;Byington et al, 2002;Ferronato et al, 2012;Iyer et al, 2006;Noyola & Demmler, 2000) and adult (Barenfanger et al, 2000;D'Heilly et al, 2008;Falsey et al, 2007) populations. Their cost-effectiveness was also shown with both populations (Barenfanger et al, 2000;Woo et al, 1997).…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Several studies have been performed to assess the clinical impact of rapid influenza testing, and these Several randomized studies compared triage-based protocol testing (ie, test results were available before the patient was seen) with standard care, and, although the results of these trials were mixed, they suggest that the availability of a rapid influenza test can decrease diagnostic evaluation, antibiotic utilization, and both the length and cost of visit in the emergency room. [56][57][58][59][60][61] Results were most pronounced for individuals testing positive for influenza, but not all studies performed this analysis, and trials were not necessarily powered to make these comparisons. All of these studies looked at only pediatric patients in an emergency room/urgent care setting.…”
Section: Factors To Considermentioning
confidence: 99%